2017
DOI: 10.1080/02670836.2017.1393204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gaseous carbon dioxide on grain refinement in Mg-8Al alloy

Abstract: A Mg-Al alloy was treated with gaseous carbon dioxide (CO2) and a refining process, and the grain refinement at each stage was investigated. The results indicated that CO2 and the subsequent refining process affect the grain refinement in the Mg-Al alloy. Moreover, the average grain size decreased from 254 to 89 µm, and the microhardness increased from 59.7 to 66.0 HV upon the addition of 9 litres of CO2. Increasing the time of the subsequent refining process to 30 min further decreased the grain size and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They reported that, due to the interaction between carbon dioxide and aluminum, Al 4 C 3 particles formed in the melt at 750 • C. The in situ-formed Al 4 C 3 particles served as nucleation sites for α-Mg grains, resulting in grain refinement and enhancement of the mechanical properties of Mg-Al alloys. Additionally, Yan Liu et al [27] reported that the addition of gaseous carbon dioxide (CO 2 ) led to grain refinement in Mg-8 wt.% Al alloys. They found that the grain refinement efficiency was primarily attributed to CO 2 gas, which facilitated the formation of Al 4 C 3 in the melt at 740 • C. The Al 4 C 3 particles were reported to act as the dominant heterogeneous nucleation substrate for α-Mg grains.…”
Section: Carbon Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that, due to the interaction between carbon dioxide and aluminum, Al 4 C 3 particles formed in the melt at 750 • C. The in situ-formed Al 4 C 3 particles served as nucleation sites for α-Mg grains, resulting in grain refinement and enhancement of the mechanical properties of Mg-Al alloys. Additionally, Yan Liu et al [27] reported that the addition of gaseous carbon dioxide (CO 2 ) led to grain refinement in Mg-8 wt.% Al alloys. They found that the grain refinement efficiency was primarily attributed to CO 2 gas, which facilitated the formation of Al 4 C 3 in the melt at 740 • C. The Al 4 C 3 particles were reported to act as the dominant heterogeneous nucleation substrate for α-Mg grains.…”
Section: Carbon Sourcesmentioning
confidence: 99%
“…The in situ-formed Al4C3 particles served as nucleation sites for α-Mg grains, resulting in grain refinement and enhancement of the mechanical properties of Mg-Al alloys. Additionally, Yan Liu et al [27] reported that the addition of gaseous carbon dioxide (CO2) led to grain refinement in Mg-8 wt.% Al alloys. They found that the grain refinement efficiency was primarily attributed to CO2 gas, which facilitated the formation of Al4C3 in the melt at 740 °C.…”
Section: Carbon Sourcesmentioning
confidence: 99%
“…The inclusion of recent examples of simulations applied to Al and Mg alloys adds greatly to the value of the review. The original research articles that follow are then loosely grouped according to subject, commencing with studies on underpinning metallurgy [2][3][4][5], cast alloys [6][7][8], the properties and performance of extruded products [9][10][11][12], before moving to parallel tubular angular pressing [13] and selective laser melting [14]. The remaining articles deal with materials that may be considered to be composites based on an aluminium alloy, and these include an important contribution on foams [15], as well as contributions on synthesis [16] and the response of a composite to liquid-phase pulse impact treatment [17].…”
Section: Light Alloysmentioning
confidence: 99%